Linear and Nonlinear Waves (an Elementary Introduction to Theory of Hamilton’s Variables with Applications to Plasma Physics and Astrophysics) - Kontorovich, V. M. (Видавничий дім «Академперіодика», 2013)
Линейные и нелинейные волны (элементарное введение в теорию гамильтоновых переменных с приложениями к физике и астрофизике)